A novel upconverison phosphor Gd2Mo4O15:Yb3+, Ho3+: intense red emission and ratiometric temperature sensing under 980 nm excitation. (27th June 2018) - Pang, Tao; Huang, Zejun
Abstract: In this paper, a novel upconversion phosphor is reported. Based on XRD and EDS, it is confirmed that the phosphor is monoclinic Gd2 Mo4 O15 :Yb 3+, Ho 3+ with P21/c space group. The non-radiation decay of 5 I6 to 5 I7 dominants the depopulation of 5 I6, thus the phosphor produces the red upconversion emission with high emission intensity and good color quality, and shows the favorable temperature sensing property. When using non-continuous excitation mode, the temperature sensitivity is determined as 0.0452 K −1 . Because the sensitivity is the same at any temperature, the new upconversion material may have greater potential for temperature sensing application than Er 3+ doped upconverison materials.